2016
DOI: 10.3389/fpls.2016.01281
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Pepper (Capsicum annuum) Revealed a Role of 24-Epibrassinolide in Response to Chilling

Abstract: Brassinosteroids (BRs) have positive effects on many processes during plant growth, development, and various abiotic stress responses. However, little information is available regarding the global gene expression of BRs in response to chilling stress in pepper. In this study, we used RNA sequencing to determine the molecular roles of 24-epibrassinolide (EBR) during a chilling stress response. There were 39,829 transcripts, and, among them, 656 were differently-expressed genes (DEGs) following EBR treatment (Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 70 publications
8
56
0
Order By: Relevance
“…5a, b). It correspond with the data of Li et al (2016) showing that exogenous application of BR activates the expression of cellular redox homeostasis-related genes, including GSTX1 (probable glutathione S-transferase). The encoded enzyme regulates conjugation of reduced glutathione (the most abundant cellular LMW AOX) to various substrates for cell detoxification.…”
Section: Correlation Analysis Among Stress Tolerance Level Phytohormsupporting
confidence: 89%
“…5a, b). It correspond with the data of Li et al (2016) showing that exogenous application of BR activates the expression of cellular redox homeostasis-related genes, including GSTX1 (probable glutathione S-transferase). The encoded enzyme regulates conjugation of reduced glutathione (the most abundant cellular LMW AOX) to various substrates for cell detoxification.…”
Section: Correlation Analysis Among Stress Tolerance Level Phytohormsupporting
confidence: 89%
“…Brassinosteroids (BRs), as polyhydroxylated steroidal plant hormones, are involved in plant physiological processes [14,48]. This present study extends our previous work on EBR in the regulation of chilling tolerance from hormone metabolism, calcium signaling transduction, and cellular redox homeostasis [19,49]. Here, we have demonstrated the positive role of EBR in enhancing plant growth and development through maintaining higher photosynthetic capability and nitrogen metabolism (Figure 8).…”
Section: Discussionsupporting
confidence: 82%
“…According to our data, as a representative hormone associated with senescence, JA significantly increased in PS compared with NS, indicating that the JA biosynthesis pathway is one of the factors involved in premature cotton senescence. Furthermore, a previous study showed that low temperatures can elevate the levels of JA [ 31 , 59 ], indicating that it may also be closely related to cold temperatures in this study. Therefore, JA may be a hormonal trigger while simultaneously accelerating leaf senescence.…”
Section: Discussionsupporting
confidence: 62%